Good farming practices in Tauramena, Colombia (Revista Sistemas de Producción Agroecológicos, 2016)
The demands of globalization have shown the importance and necessity of reconvert the Colombian livestock in more competitive production systems, with a long-term business vision and an internal organization designed to meet the needs of its customers. In response to the demands of national and international markets Colombia has initiated a process of improvement of health standards in the primary production of meat and bovine milk, giving way to the implementation of good livestock practices (GMP) by the municipal administration of Tauramena, Casanare the accompaniment was performed to producers who were interested in the program, seeking to take advantage of new technologies to produce meat and milk of excellent quality protecting the health of consumers, workers and animals. The work was done in collaboration with the Institute for Development Agribusiness of Tauramena (IFATA) within the framework of compliance of livestock technical assistance provided by the municipal government to small and medium producers to whom it is given the opportunity to participate in activities such as: technical assistance, characterization of buildings, checklist, improvement plans and health, learning paths, domestic livestock tour, agricultural field school (ECAS), and by-product processing practice, it was confirmed that meat producers are 387 who handle zebu breeds, the amount of land dedicated to milk production is 54 where races Girolando, Simmenthal and Swiss Brown are used and the dual purpose system has a total of 170 who perform this task with animals of Zebu, Holstein and Swiss brown crosses. It was possible to conclude that the characterization of the properties is one of the most important goals for municipal administration since the activity allows know the current state of the livestock sector and that updates must also be done constantly due to the fluctuation of livestock activity; as regards the producers who were part of the GPM program understood that it seeks to ensure the welfare of animals and the safe production of food.
Keywords: livestock; cattle; safety; health; food